Prohet Muhammad approach in dealing with wrongdoers : an analytical study مناهج النبي صلى الله عليه وسلم في التعامل مع المخطئ: دراسة تحليلية - Islami, Md Fakhrul; Mohammed, Saad Eldin Mansor (IIUM Press, 2020)
This paper aims to glean testaments that defined on Prophet Muhammad (PBUH) manners in addressing people's wrongdoing or sins. This is because we live in an era where we face many problems due to the absence of these approaches in our lives. The study was divided into a brief introduction and several sub-topics th atrepresent the different approached of the Prophet (SAW) and his followers in dealing with those who committed sins. This study adopted an approach of library research method with content analysis. Among the most important conclusions are that most of the methods in dealing with those who made wroingdoing are based on wisdom, good advice, soft behaviour and characteristic, meeting, discussing and so on. These are the most important outcomes from this reserach. The researcher hopes that this research would contribute to a positive solution in respond to conflicts when we are going to deal with people misdeed.